2021
DOI: 10.3390/cancers13225613
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ1 Secreted by Cancer-Associated Fibroblasts as an Inductor of Resistance to Photodynamic Therapy in Squamous Cell Carcinoma Cells

Abstract: As an important component of tumor microenvironment, cancer-associated fibroblasts (CAFs) have lately gained prominence owing to their crucial role in the resistance to therapies. Photodynamic therapy (PDT) stands out as a successful therapeutic strategy to treat cutaneous squamous cell carcinoma. In this study, we demonstrate that the transforming growth factor β1 (TGFβ1) cytokine secreted by CAFs isolated from patients with SCC can drive resistance to PDT in epithelial SCC cells. To this end, CAFs obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Recent studies have the important regulatory roles of CAFs in tumor immune response, which could affect the anti-tumor activity of tumor-infiltrating immune cells [ 32 , 33 ]. In solid tumors, CAFs could recruit and stimulate immunosuppressive cells, and induce the formation of dense extracellular matrix (ECM), consequently affecting the anti-tumor immunity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have the important regulatory roles of CAFs in tumor immune response, which could affect the anti-tumor activity of tumor-infiltrating immune cells [ 32 , 33 ]. In solid tumors, CAFs could recruit and stimulate immunosuppressive cells, and induce the formation of dense extracellular matrix (ECM), consequently affecting the anti-tumor immunity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gallego-Rentero, M. et al [ 1 ] conducted research focused on the role of the tumor microenvironment (TIME) in the resistance to Photodynamic therapy (PDT). In particular, the authors evaluated the role of TGFβ1 produced by cancer-associated fibroblasts (CAFs).…”
Section: Clinical Snippetsmentioning
confidence: 99%
“…As a major secreted factor of CAFs, TGFβ predominantly mediates the crosstalk between CAFs and cancer cells. Several in vitro studies have demonstrated that, in OSCC and CSCC, the TGFβ secreted by CAFs induces EMT and resistance to different therapies [ 71 , 72 , 73 , 74 , 75 ].…”
Section: Tumor Microenvironmentmentioning
confidence: 99%